Correction to: Identifying Outstanding Transition-Metal-Alloy Heterogeneous Catalysts for the Oxygen Reduction and Evolution Reactions via Subgroup Discovery (Topics in Catalysis, (2022), 65, 1-4, (196-206), 10.1007/s11244-021-01502-4) - Foppa, Lucas; Ghiringhelli, Luca M. (Topics in Catalysis, 2022)
The original version of this article unfortunately contained an error and it is corrected with this erratum.
CRIS-Team Scopus Importer:2023-09-25